2013 IEEE Wireless Communications and Networking Conference (WCNC) 2013
DOI: 10.1109/wcnc.2013.6554679
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of receiver based MAC using configurable framework in WSNs

Abstract: Receiver-based MAC (RB-MAC) is a preamblesampling MAC protocol for WSNs in which a receiver node is dynamically elected, among potential neighbors of the sender node, based on current channel conditions. In this paper, we evaluate the performance of RB-MAC and compare it with a senderbased preamble-sampling MAC protocol by using analytical methods, and implementation in real sensor nodes. We have used Configurable MAC (C-MAC), which is a framework to develop different MAC protocols in WSNs. This framework is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In some literature different terminologies have been used for Preamble Sampling approach, for example, cycled receiver [8] and channel polling [9]. Some MAC protocols that utilised this idea are, for example, Berkeley MAC (BMAC) [4], Wireless Sensor MAC (WiSeMAC) [10], 1‐hopMAC [11] and RB‐MAC [1, 3]. The sparse topology and energy management [12] protocol uses two channels: a wakeup channel and a data channel and other protocols such as carrier sense multiple access (CSMA) with minimum preamble sampling (CSMA‐MPS) [13], transmitted initiated cycled receiver [8], XMAC [14] and multimod‐hybrid MAC [15] use techniques to reduce preamble length by packetisation.…”
Section: Preamble Sampling Mac Protocol (Ps‐mac)mentioning
confidence: 99%
See 1 more Smart Citation
“…In some literature different terminologies have been used for Preamble Sampling approach, for example, cycled receiver [8] and channel polling [9]. Some MAC protocols that utilised this idea are, for example, Berkeley MAC (BMAC) [4], Wireless Sensor MAC (WiSeMAC) [10], 1‐hopMAC [11] and RB‐MAC [1, 3]. The sparse topology and energy management [12] protocol uses two channels: a wakeup channel and a data channel and other protocols such as carrier sense multiple access (CSMA) with minimum preamble sampling (CSMA‐MPS) [13], transmitted initiated cycled receiver [8], XMAC [14] and multimod‐hybrid MAC [15] use techniques to reduce preamble length by packetisation.…”
Section: Preamble Sampling Mac Protocol (Ps‐mac)mentioning
confidence: 99%
“…In [1] it has been demonstrated that RB‐MAC maintained almost the same level of reliability with less energy consumption compared with a sender‐based MAC (SB‐MAC) protocols. In [3], the authors presented a practical implementation of RB‐MAC and recognised the energy performance of RB‐MAC against B‐MAC [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some MAC protocols that utilised this idea are, for example, BMAC (Berkeley MAC) [5], wireless sensor MAC [11], 1hopMAC [12] and RBMAC [3, 4]. The Sparse Topology and Energy Management [13] protocol uses two channels: a wakeup channel and a data channel and other protocols such as CSMA with minimum preamble sampling [14], transmitted initiated cycled receiver [9], XMAC [15] and multimod‐hybrid MAC [16] use techniques to reduce preamble length by packetisation.…”
Section: Ps‐mac Protocolmentioning
confidence: 99%
“…In RB‐MAC [3, 4], a sender node transmits its data without defining the address of a particular node as a receiver. All the neighbouring nodes within communication range of the sender node receive the data packet.…”
Section: Ps‐mac Protocolmentioning
confidence: 99%
See 1 more Smart Citation